Impact of internal controls on execution of payroll system :A case study of Ministry of Finance and Economic Affairs – Zanzibar (MoFEA) - Ahmada, Ridhwan I. (Mzumbe University, 2024)
A dissertation submitted to the school of business in fulfillment of the requirements for award of the Degree of Master of Science in Accounting and Finance (MSc A&F) of Mzumbe University.